2001
DOI: 10.1046/j.1460-9568.2001.01385.x
|View full text |Cite
|
Sign up to set email alerts
|

Action observation activates premotor and parietal areas in a somatotopic manner: an fMRI study

Abstract: Functional magnetic resonance imaging (fMRI) was used to localize brain areas that were active during the observation of actions made by another individual. Object-and non-object-related actions made with different effectors (mouth, hand and foot) were presented. Observation of both object-and non-object-related actions determined a somatotopically organized activation of premotor cortex. The somatotopic pattern was similar to that of the classical motor cortex homunculus. During the observation of object-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

104
1,102
9
27

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,254 publications
(1,251 citation statements)
references
References 23 publications
(23 reference statements)
104
1,102
9
27
Order By: Relevance
“…Brain areas with mirror properties have also been discovered in the human parietal and premotor cortices (e.g., Grèzes et al 2003;Iacoboni et al 1999;Koski et al 2002;Leslie et al 2004). Consistent with the present findings of body part specific mirroring effects, these brain structures are somatotopically organized and represent foot and hand actions in anatomically distinct areas (Buccino et al 2001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Brain areas with mirror properties have also been discovered in the human parietal and premotor cortices (e.g., Grèzes et al 2003;Iacoboni et al 1999;Koski et al 2002;Leslie et al 2004). Consistent with the present findings of body part specific mirroring effects, these brain structures are somatotopically organized and represent foot and hand actions in anatomically distinct areas (Buccino et al 2001).…”
Section: Discussionsupporting
confidence: 89%
“…Imaging studies have confirmed that a similar system is also present in humans (e.g. Grèzes et al 2003;Buccino et al 2001;Iacoboni et al 1999;Koski et al 2002), and this system has been linked to the automatic imitation of actions by imaging and behavioral studies (e.g., Jackson et al 2006;Leslie et al 2004;Wohlschläger and Bekkering 2002).…”
Section: Introductionmentioning
confidence: 79%
“…In fact the dorsal prefrontal (pre-motor) peaks showing increased activation for counting with respect to estimation in the present study correspond to peaks previously associated to movements of the hand (while more ventral regions are associated with movements of the mouth, congruently with the classical motor organization of the region (Buccino et al, 2001). …”
Section: Countingsupporting
confidence: 87%
“…While frequently ventral premotor cortices have been associated with movement observation (Decety and Grèzes, 1999), the presently observed more dorsal premotor activations have been reported before particularly for the observation of wrist and hand movements (Buccino et al, 2001;Morin and Grezes, 2008;Sakreida et al, 2005). Interestingly, the presently observed areas were part of a network showing increased activation in response to rehabilitation using action observation (Ertelt et al, 2007).…”
Section: Observationsupporting
confidence: 49%
“…In more detail, previous research indicated that activation evoked by movement observation may potentially be reduced when the movement is simple (Biagi et al, 2010), does not involve objects (Buccino et al, 2001;Morin and Grezes, 2008), and when the instruction does not stress that the movements are supposed to be imitated after having been watched (Frey and Gerry, 2006) (but see Caspers et al, 2010). Thus, by using other actions and instructions we may have had observed stronger activation of the sensorimotor system, potentially resulting in a better resemblance of Execution.…”
Section: Observationmentioning
confidence: 92%